Analysis of Insurtech Innovation Development in Accelerating The Claim Process and Improving Service For Insurance Participants at PT. Chubb Life Medan - Silvia Retri Aldona Tampubolon; Muhammad Arif; Nurul Jannah (Dinasti Publisher, 2024)
The development of innovation in the insurtech industry has become important in improving the efficiency of the claims process and services for insurance participants. This study aims to analyze the development of insurtech innovation in accelerating the claims process and improving services for insurance participants at PT Chubb Life Medan. The research method used is a case study by conducting interviews and direct observation of the claims process and existing services. The results showed that the use of technology in the form of mobile applications and online platforms has succeeded in accelerating the claims process and increasing the satisfaction of insurance participants. The implication of this research is the need to continue to encourage the development of insurtech innovation to improve efficiency and quality of service for insurance participants at PT Chubb Life Medan.